Profil Tingkatan Mathematical Habits of Mind Peserta Didik dalam Penerapan Model Pembelajaran Means-Ends Analysis - Imaniah, Siti; Ihsan, Iden Rainal (xxxx-xxxx)
The backgroud of this research is the need for Mathematical Habits of Mind (MHM of Â students to solve mathematicâs problems. The aim of this study is to find out the MHM level profile / criteria of students after implementation the Means Ends-Analysis learning model. This study uses qualitative approach. The method used is descriptive method. The subject of the research was the eighth grade students of Public Middle School in the city of Bandung. The instrument used is MHM questionnaire. The conclusion of this study is that the MHM level profile / criteria of students using MEA learning has a strong category